(untitled) (Agricultural Engineering, 2018)
The article presents the results of two-year studies on the influence of the method of sowing and the level of nitrogen application on the yield of seeds of Silphium perfoliatum L. − a new fodder crop for the conditions of Belarus. Silphium is precious for the nutritive value of green mass. According to the literature sources, dry matter contains 16-28% of protein, more than 60% of nitrogen-free extractives, 13-23% of sugars, high content of mineral substances, a small amount of fiber, adequate calcium and phosphorus, carotene, vitamin C. Mineral composition of Silphium contains 17.6% of dry matter, including 152.3 mg·kg−1 of ash. Macro elements: calcium – 18.1, phosphorus − 2.55, manganese – 4.48, potassium – 24.03, sodium – 0.40, sulphur – 0.40 mg· kg−1 of mg· kg−1 of dry matter. The mass of 1000 seeds was from 23.7 to 25.5 g. The seed germination was good and varied from 75% to 84%. It has been established that the best way to sow the Silphium is planting seedlings according to the 70x30 scheme. This option ensured the yield of seeds of 3.6 and 3.7 c/ha. The applying of increased doses of nitrogen fertilizers N90 and N120 and sowing seeds ensured the yield of seeds ranging from 3,6 to 3,9 c·ha−1.